2018
DOI: 10.24998/maeusabed.435383
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Varroa destructor (Family: Varroidae) prevalent in honeybees (Apis mellifera) in the province of Aydin in Turkey

Abstract: The aim of the present study was to identify the haplotypes of the Varroa destructor mite which infects honeybees (Apis mellifera) in the province of Aydın in Turkey, using two different modified techniques for the mitochondrial Cox1 gene of the mite. In order to confirm the haplotype, two different primer pairs were selected. 376 bp DNA in size was amplified using the first primer pair. SacI restriction enzyme was applied to the amplified products; however, this restriction enzyme did not cut the DNA. 570 bp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The comparison of 332 COI sequences analyzed in the present study revealed very high similarity (only 0.06% variation), supporting the evolutionary history of V. destructor . Similar to previous findings in Türkiye (Warrit et al 2004 ; Ayan and Aldemir 2018 ; Koç et al 2021 ), all V. destructor populations investigated in the present study belonged to Korean haplotype. To provide a broader perspective, we conducted a haplotype analysis using over 300 sequences from worldwide populations of Varroa mites (Fig.…”
Section: Resultssupporting
confidence: 92%
“…The comparison of 332 COI sequences analyzed in the present study revealed very high similarity (only 0.06% variation), supporting the evolutionary history of V. destructor . Similar to previous findings in Türkiye (Warrit et al 2004 ; Ayan and Aldemir 2018 ; Koç et al 2021 ), all V. destructor populations investigated in the present study belonged to Korean haplotype. To provide a broader perspective, we conducted a haplotype analysis using over 300 sequences from worldwide populations of Varroa mites (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Another switch event occurred around 1957, leading to the creation of a second haplotype, the Japanese haplotype [ 45 ]. Both haplotypes (with a dominance of the Korean haplotype) first colonized the west of their countries of origin [ 46 , 47 , 48 , 49 ] and they are now present all around the world. These host switch events did not occur without any genetic changes.…”
Section: Discussionmentioning
confidence: 99%